Cyclic Nucleotide-Gated Ion Channel 6 Mediates Thermotolerance in Arabidopsis Seedlings by Regulating Hydrogen Peroxide Production via Cytosolic Calcium Ions - Wang, Wenxu; Zhang, Jiaojiao; Ai, Lijuan; Wu, Dan; Li, Bing; Zhang, Lingang; Zhao, Liqun (Frontiers in Plant Science, 2021)
We previously reported the involvement of cyclic nucleotide-gated ion channel 6 (CNGC6) and hydrogen peroxide (H2O2) in plant responses to heat shock (HS). To demonstrate their relationship with plant thermotolerance, we assessed the effect of HS on several groups of Arabidopsis (Arabidopsis thaliana) seedlings: wild-type, cngc6 mutant, and its complementation line. Under exposure to HS, the level of H2O2 was lower in the cngc6 mutant seedlings than in the wild-type (WT) seedlings but obviously increased in the complementation line. The treatment of Arabidopsis seeds with calcium ions (Ca2+) increased the H2O2 levels in the seedlings under HS treatment, whereas treatment with a Ca2+ chelator (EGTA) inhibited it, indicating that CNGC6 may stimulate the accumulation of H2O2 in a manner dependent on an increase in cytosolic Ca2+ ([Ca2+]cyt). This point was verified by phenotypic observations and thermotolerance testing with transgenic plants overexpressing AtRbohB and AtRbohD (two genes involved in HS-responsive H2O2 production), respectively, in a cngc6 background. Real-time reverse transcription-polymerase chain reactions and Western blotting suggested that CNGC6 enhanced the gene transcription of HS factors (HSFs) and the accumulation of HS proteins (HSPs) via H2O2. These upon results indicate that H2O2 acts downstream of CNGC6 in the HS signaling pathway, increasing our understanding of the initiation of plants responses to high temperatures.